Reorientasi Konstitusional Perlindungan Pers di Indonesia dalam Menegaskan Prinsip Kebebasan Berekspresi - Sultoni Fikri; Anggit Wasesa Praja; Gatot Hadi Purwanto; Ahlan Ramadana (Pustaka Peradaban, 2026)
The criminalization of the press remains a significant issue in Indonesia's law enforcement practice, particularly when journalistic work is subjected directly to criminal or civil proceedings without first applying the dispute resolution mechanism established under Law Number 40 of 1999 on the Press. This problem stems from the ambiguity of the phrase